Acceptability and willingness to pay for contingency management interventions among parents of young adults with problematic opioid use. (1st January 2020) - Ryan-Pettes, Stacy R.; Devoto, Amanda; DeFulio, Anthony
Highlights: Parents of opioid using young adults have positive perceptions of incentives. Parents of opioid using young adults are willing to pay for CM services. Parents of opioid using young adults believe CM services would be beneficial. Abstract: Background: There is a need for new research addressing the cost prohibitive nature of maintaining contingency management (CM) in community settings. While researchers propose managed care as an option to support costs, there is no research on self-pay models. To inform such research, it is important first to understand client willingness to pay for CM services. We examine acceptability and willingness to pay for CM services among parents with and without young adult children with problematic opioid use. Methods: A web-based survey was administered to a sample of parents of adult children ages 18–35 with (target sample) and without (comparison sample) a history of problematic opiate use. Results: One hundred thirty parents participated ( n target = 30; n comparison = 100) and were predominately white, college educated, and of higher income. Findings showed a high proportion of participants had positive opinions of using incentives for substance use treatment and would consider incentive-based treatments for their child. Most participants reported they would be willing to pay for CM at levels consistent with amounts used in efficacious programs but expressed worry that incentives would be used to buy drugs. Most participants reported this worry would be eased if incentives were delivered via reloadable gift cards and if incentives were only delivered during periods of abstinence. Conclusions: This is the first study to examine parent perceptions of incentives and acceptability and willingness to pay for CM services. Results suggest self-pay models for disseminating CM to young adults with problematic opioid use may be an option.